RESPON FISIOLOGIS DAN PALATABILITAS DOMBA EKOR TIPIS TERHADAP LIMBAH TAUGE DAN KANGKUNG KERING SEBAGAI PAKAN PENGGANTI RUMPUT - Listya Purnamasari; Sri Rahayu; Muhammad Baihaqi (Universitas Tidar, 2018)
Physiological response are influenced by environmental conditions, such as climate change and the feed. Limitied of land crop and farm cause difficulties to find grass as fiber feed. This research aimed to study the effect of dried kale and bean sprouts waste for substitution the grass on the physiological response of male javanese thin thailed sheep (under one years old) and their palatability. Feed treatment were : P1 (50% concentrate+50% grass), P2 (50% concentrate+50% dried kale), and P3 (50% concentrate+50% bean sprouts waste) respectively. The parameters were palatability, rectal temperature, heartbeat and respiration frequency. Analyze method used completely randomized design with three treatments of feeding and 4 replications was used. Data processed by ANOVA and Tukey’s for further test. The experimental result showed that feed treatment were not significant (P>0.05) to rectal temperature, heartbeat and respiration frequency. The best palatability seen on P2 feed (50% consentrate + 50% mung bean sprout waste). The conclusion were bean sprout waste and dried kale can be used to substitute grass, they had a good palatability and they did not give bad effect to physiological of javanese thin tailed sheep.The conclusion of this study, bean sprout waste and dried kale has a good palatability and were not significant to physiological response of javanese thin tailed sheep so it can be used to substitute grass.Keywords: dried kale, physiological responses, javanese thin tailed sheep, bean sprout waste, palatability